2019
DOI: 10.1007/s10353-019-0586-9
|View full text |Cite
|
Sign up to set email alerts
|

Management of blunt hepatic and splenic trauma in Austria: a national questionnaire study

Abstract: Background Treatment of hepatic and splenic injuries has significantly evolved over the past 30 years: Nonoperative management (NOM) has increasingly become standard of care for the majority of patients in specialised centres. However, patient selection and details of practical management such as time to reinitiating oral intake, duration of restricted activity, or necessity of repeated imaging are still a matter of debate. This national multicentre questionnaire study aims to give a cross-sectional overview o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Modern coagulation management, including thromboelastography to guide blood product resuscitation, contributed to improved outcomes for NOM at our center. According to an Austrian survey in 2016, the rate of NOM was > 50% in more than two thirds of all national hospitals and an increasing trend towards radiologic interventions was reported [30].…”
Section: Discussionmentioning
confidence: 99%
“…Modern coagulation management, including thromboelastography to guide blood product resuscitation, contributed to improved outcomes for NOM at our center. According to an Austrian survey in 2016, the rate of NOM was > 50% in more than two thirds of all national hospitals and an increasing trend towards radiologic interventions was reported [30].…”
Section: Discussionmentioning
confidence: 99%
“…Several topics related to the follow-up of these patients are still controversial. These include the frequency of clinical reevaluations and laboratory tests, the duration of patient monitoring, transfusion thresholds that would indicate intervention (surgery or angiography), time to iniciate venous thromboembolism (VTE) prophylaxis, the time of bed rest and hospital stay, the need for immunization after spleen embolization and after extensive splenic injury submitted to NOM, the indication of control imaging and outpatient follow-up after hospital discharge 5 , 7 , 18 .…”
Section: Introductionmentioning
confidence: 99%
“…As with non-operative treatment of other abdominal organs, there is some concern in initiating prophylaxis due to the risk of rebleeding and failure of NOM 51 . However, studies have shown that it is safe to introduce VTE chemoprophylaxis within the first 48h-72h of hospital admission 18 , 49 , 51 , 52 without increasing the incidence of failure of NOM 52 . Joseph et al 49 observed a tendency towards a higher incidence of thromboembolic complications in patients receiving late prophylaxis (after 72h), although this difference was not statistically significant.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations